Longitudinal static stability analysis with wing swept angle variation of UAV flying wing surveillance adelaar 2 use software XFLR 5 - Lesalli, Prytha Virgiawan; Cahyono, M. Ardi (Institut Teknologi Dirgantara Adisutjipto, 2020)
Aircraft stability is very important for calculated in aircraft design, specially for UAV which will be used for air surveillance. The purpose of aircraft stability analysis to find aircraft stability characteristic. Aircraft static stability can be analyzed by XFLR 5 Software which is can calculate characteristic of aircraft static stability, show visual, graph, and simulation of aircraft stability. Adellar 2 is UAV with flying wing configuration and will be analyzed use software XFLR 5 with the input of aircraft mass with the centre of gravity wil be located in 5% of mean aerodynamic chord in front of neutral point and aircraft geometry types of airfoil in chord root, tip, span , winglet geometry and wing swept. With the result that Adelaar 2 is qualify for longitudinal static stability after the author analyze use XFLR5 with the parameter Cma<0 and obtained character of stability for 22.5o , 25o , 27.5o and 30o wing swept angle.